(untitled) (Journal of Academic Research, 2024)
Abstract The study aimed to show the spatial characteristics of the locations of basic education schools in the municipal branch of Shuhada Al-Rumaila, which represents the city center geographically, service-wise, economically and demographically, using spatial analysis tools provided by geographic information systems technology, and using ideal standards for designing schools. It also aimed to reveal the extent of conformity the locations of those schools and the criteria and foundations for their establishment. The study concluded a number of results, including: The geographical distribution pattern of basic education schools in the Rumaila branch is a dispersed pattern, with a probability of less than 5% that the reason for this dispersion is due to randomness. The area of the served areas in the study area, at a range of 500 m, was about 10 km2, or 33.3%, of the area of the study area. The students’ share of the total and covered school area did not conform to the standards for the design and construction of basic education schools. Keywords: spatial analysis, design standards - actual and ideal central centers - spatial sanctuary - distribution direction